THE ELLIPTICITIES OF GALAXIES IN GALAXY CLUSTERS OF DIFFERENT MORPHOLOGICAL TYPE - Panko, E. A.; Flin, P. (Одеські астрономічні публікації, 2014)
The distribution of galaxy ellipticities was analyzed for 207 rich PF galaxy clusters found in the Munster Red Sky Survey Galaxy Catalogue. Clusters with BM types from a comparison with the ACO catalogue were also classified on the new scheme. The new morphological types take into consideration concentration towards the cluster center, indicationsof a preferential direction or plane, and the role of the brightest cluster galaxies. Differences in the distribution of galaxy ellipticities for individual clusters are statistically significant, in contrast to the average distribution of ellipticities for galaxies belonging to clusters of different morphological type. Two types of galaxy ellipticity distribution were found: single-modeand bimodal. The distributions apparently reflect different contributions from spiral and elliptical galaxies. The shapes of galaxies in individual clusters appear to relate to local conditions.